The impact of cystic fibrosis on the immunologic profile of pediatric patients - Daniela M. Bernardi; Antonio F. Ribeiro; Tais N. Mazzola; Maria M.S. Vilela; Valdemiro C. Sgarbieri (Brazilian Society of Pediatrics, 2013)
Objective: To compare the immunologic state of 44 pediatric patients with cystic fibrosis (CF) with a control group consisting of 16 healthy individuals. Methods: CF patients aged 3 to 12 years with moderate to good clinical score were selected for the study. Erythrocytic glutathione, production of reactive oxygen species, cytokines (TNF-a, IFN-g, IL-8, IL-6, IL-10) in peripheral blood mononuclear cells cultures under spontaneous and BCG- or PHA-stimulated conditions, serum concentrations of TGF-b2, IgA, IgG, IgM, IgE, and salivary IgA were evaluated. Results: The spontaneous production of TNF-a, IL-6, and IL-10, the PHA-stimulated production of IL-6, and the serum TGF-b2, IgA, and IgG were increased in samples from CF patients. Healthy subjects had a higher production of TNF-a in response to BCG. Conclusion: Although CF patients appeared clinically stable, the results of their peripheral blood examinations demonstrated an impact on the immune system.